Eksistensi Cerita Rakyat Sebagai Media Pembentukan Karakter Siswa Sekolah Dasar - Rukayah Rukayah (Universitas Negeri Makassar, 2018)
The purpose of this paper is to explain the existence of folklore as a medium for character building for students, especially in elementary school. Folk stories have noble values in society. Therefore, it is very appropriate to be used as a medium in shaping character especially for elementary school children. Various character characters depicted in the story can be imitated or imitated by children, usually good contrasting characters are portrayed with evil characters, so that students / readers hate and hostile to evil figures, even curse them, otherwise good characters are lauded and even imitated by their actions. This shows, that the mind and feelings are directly involved naturally. Therefore, it is advisable to keep a fairytale culture before going to sleep, because children can ask questions directly or give feedback about what has been heard from the narrator, while helping to preserve the native culture of the archipelago.